Growth root-knot nematode infestation and phosphorus nutrition in Piper Nigrum (L.) as influenced by vesicular arbusclar mycorrhizae - Sivaprasad, R. (Malaysian Plant Protection Society, 2013)
Effect of innoculation with VA mycorrhizal fungi Glomus fasciculatum and G. etunicatum on root knot nematode Meloidogyne incognita infestation, growth and phosphorus uptake of Piper nigrum (L) was examined. There was remarkable reduction in root-knot index and nematode count in the root tissue and rhizosphere soil of pepper plants pre-inoculated with VAM fungi. Plants inoculated with mycorrhizal fungi were taller and had more shoot and root weights and phosphorus content. Nematode inoculation significantly reduced the growth and root development. However, the plants pre-inoculated with VAM even under inoculation with root-knot nematode recorded a significantly increase in dry weight of shoot and root over nematode alone inoculation. M. incognita did not influence the mycorrhizal infection and spore count. a negative relationship was obseved between VAM colonisation and intensity of nematode infestion